2016
DOI: 10.1016/j.yrtph.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the benefits of using read-across and in silico techniques to fulfill hazard data requirements for chemical categories

Abstract: Substantial benefits are realized through the use of read-across and in silico techniques to fill data gaps for structurally similar substances. Considerable experience in applying these techniques was gained under two voluntary high production volume (HPV) chemical programs - the International Council of Chemical Associations' (ICCA) Cooperative Chemicals Assessment Programme (with the cooperation of the Organization of Economic Cooperation and Development) and the U.S. Environmental Protection Agency's HPV C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
0
22
0
4
Order By: Relevance
“…In addition, about 75% of European Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) dossiers submitted between 2010 and 2013 contain read-across for at least one endpoint (Ball et al, 2016). The read-across method is endorsed by other regulatory authorities worldwide including the Research Institute for Fragrance Materials, the International Council of Chemical Associations (ICCA) and the U.S. Environmental Protection Agency's High Production Volume (HPV) Challenge Program (Bishop et al, 2012;Stanton and Kruszewski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, about 75% of European Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) dossiers submitted between 2010 and 2013 contain read-across for at least one endpoint (Ball et al, 2016). The read-across method is endorsed by other regulatory authorities worldwide including the Research Institute for Fragrance Materials, the International Council of Chemical Associations (ICCA) and the U.S. Environmental Protection Agency's High Production Volume (HPV) Challenge Program (Bishop et al, 2012;Stanton and Kruszewski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used for regulatory purposes: a properly used model can predict whether a new chemical can be harmful to people and the environment even without the use of experimental techniques, so the registration of a chemical can be denied or sought, or new safety instructions can be deferred. 91,118 Many literature examples 36,[119][120][121][122][123][124][125][126] have shown how these methods are associated with regulatory issues. Mechanism of action experimental determination is time-consuming and expensive.…”
Section: Resultsmentioning
confidence: 99%
“…(See further information on the OECD's work on "omics" technologies in Section 5.8.) Read-across and similar approaches can fill data for requirements for chemical categories as well as eliminate the need for many animal tests (Stanton and Kruszewski, 2016).…”
Section: Enhancing Hazard Assessment Methodsmentioning
confidence: 99%
“…The same methods used to estimate costs and cost savings above as a result of MAD and (Q)SARs/read-across can be applied to estimate the number of animals used for testing. Based on this approach, this report suggests a substantial reduction (56%) in the number of test animals that are needed ( Stanton and Kruszewski (2016) found that through the use of read-across and (Q)SAR techniques to fill data gaps for 261 chemical substances, 100 000 to 150 000 test animals were not needed, and USD 50 million to USD 70 million in testing costs were avoided.…”
Section: Reducing Testing and Repeat Testing For New Industrial Chemimentioning
confidence: 99%
See 1 more Smart Citation